2015
DOI: 10.1007/s13277-015-3975-0
|View full text |Cite
|
Sign up to set email alerts
|

CPEB4 interacts with Vimentin and involves in progressive features and poor prognosis of patients with astrocytic tumors

Abstract: Cytoplasmic polyadenylation element binding protein 4 (CPEB4) is a regulator of gene transcription and has been reported to be associated with biological malignancy in cancers. However, it is unclear whether CPEB4 has any clinical significance in patients with astrocytic tumors, and mechanisms that CPEB4 contribute to progression of astrocytic tumors remain largely unknown. Here, correlation between CPEB4 expression and prognosis of patients with astrocytic tumors were explored by using qPCR, WB and IHC, and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…CPEB4 has emerged as a potential biomarker in several cancers, such as colorectal cancer, breast cancer, astrocytic tumor, non-small cell lung cancer, pancreatic cancer, and glioma. [18][19][20][21][22][23][24] In this study, we found that compared to adjacent normal brain tissues, CPEB4 protein and mRNA levels were significantly increased in glioma tissues. In addition, CPEB4 expression was positively correlated with advanced WHO grade (p < 0.001) and lower KPS score (p < 0.001).…”
Section: Discussionmentioning
confidence: 92%
“…CPEB4 has emerged as a potential biomarker in several cancers, such as colorectal cancer, breast cancer, astrocytic tumor, non-small cell lung cancer, pancreatic cancer, and glioma. [18][19][20][21][22][23][24] In this study, we found that compared to adjacent normal brain tissues, CPEB4 protein and mRNA levels were significantly increased in glioma tissues. In addition, CPEB4 expression was positively correlated with advanced WHO grade (p < 0.001) and lower KPS score (p < 0.001).…”
Section: Discussionmentioning
confidence: 92%
“…CPEB4-associated mRNAs are significantly enriched in multiple cellular functions that are relevant to tumorigenesis, including Ras-related molecules, cell signaling components, chromatin remodeling proteins, cyclins, apoptosis-related molecules, stress and inflammation factors, metabolic enzymes and genes related to cell migration and metastasis (19). In addition, CPEB4 has been reported in association with tumor growth, vascularization and invasion in invasive ductal breast carcinoma (IDC), colorectal cancer, pancreatic ductal adenocarcinoma, metastatic prostate cancer and glioblastoma (19,(49)(50)(51)(52). High expression of CPEB4 has been observed in 48.6% of IDC samples and is possibly related to increased histological grading and N stage of IDC (50).…”
Section: Cpeb4mentioning
confidence: 99%
“…Suppression of CPEB4 expression by siRNA in SW480 and LOVO colon cancer cells enhances apoptosis and decreases cellular proliferation and is associated with decreased expression of antiapoptotic protein Bcl-X and increased expression of proapoptotic protein Bax (52). CPEB4 is also overexpressed in glioblastomas but not expressed in normal astrocytes or paratumor tissues (19,49). CPEB4 down-regulation in glioma cells results in reduced tumor size, cellular proliferation and microvessel density, as well as increased apoptosis (19,49,54).…”
Section: Cpeb4mentioning
confidence: 99%
See 2 more Smart Citations